Effect of cigarette smoke exposure and cessation on regional diffusion properties in rat intervertebral discs - Joshua Kelley; Nathan Buchweitz; Avery Madden; Hongming Fan; Glenn Hepfer; Michael Kern; Danyelle M. Townsend; Tong Ye; Hai Yao; Yongren Wu (JOR Spine)
Abstract Background Cigarette smoking is a recognized risk factor for orthopedic disorders, particularly intervertebral disc (IVD) degenerative disease. However, the IVD pathophysiology, especially the spatial–temporal remodeling progression in the context of cigarette smoking, remains unclear. This study aimed to address this knowledge gap through a quantitative assessment of IVD structural composition and diffusion properties using a Sprague–Dawley rat model. Methods Twenty‐four rats were divided into control and smoke exposure cohorts, each with two sub‐groups of six rats. One smoke exposure sub‐group was sacrificed after 2 months of daily cigarette smoke exposure in a custom smoking apparatus, while the other was sacrificed after an additional 5 months of smoke cessation. The control groups were age‐matched to the smoke exposure groups. A fluorescent recovery after photobleaching (FRAP) technique was used to determine solute diffusivities and multi‐photon excitation (MPE) imaging was performed to characterize structural changes in the annulus fibrosus (AF), nucleus pulposus (NP), and cartilage endplate (CEP). Results A decrease in diffusivity was observed in the CEP and the AF (radial direction only) after 2 months of smoke exposure. MPE imaging showed aberrant CEP calcification and reduced AF radial collagen fiber bundle diameter, suggesting that the IVD exhibits regionally dependent structural remodeling due to smoke exposure. Furthermore, the smoke cessation group showed deteriorating alterations of structure and diffusivities in all three‐disc regions, including the NP, indicating that five‐month smoke cessation alone didn't reverse the progression of IVD degenerative remodeling during aging. Conclusion This study advances the understanding of IVD pathophysiology in the context of cigarette smoke exposure and cessation, laying the groundwork for potential earlier diagnosis and optimized interventions.